Case Report: Familial hypocalciuric hypercalcemia type 1 with a novel mutation combined with Gitelman syndrome and a review of the literature - He, Taoyuan; Li, Xinyu; Li, Guosheng; Wang, Wanyang; Fu, Hongjun; Gao, Zhengnan; Liu, Xuhan (Frontiers in Endocrinology, 2025)
IntroductionFamilial hypocalciuric hypercalcemia (FHH) is an autosomal dominant disorder caused by an inactivating mutation in the CASR gene, while Gitelman syndrome (GS) is an autosomal recessive renal tubular disorder resulting from a pathogenic mutation in the SLC12A3 gene. Both genetic disorders are relatively rare. This report presents a patient with both FHH and GS, exhibiting unique clinical and genetic complexities.Case summaryWe report a case of a 69-year-old Asian female patient who had previously presented to the hospital on multiple occasions with complaints of joint stiffness, fatigue, dizziness, or other symptoms. The patient was readmitted to the hospital at the age of 66, presenting with the following clinical findings: hypocalciuria, hypercalcemia, normal or mildly elevated parathyroid hormone (PTH) levels, hypokalemia, hypomagnesemia, hypophosphatemia, normal blood pressure, chondrocalcinosis (CC), and diabetes mellitus. Our careful analysis suggested that the patient might have the co-occurrence of GS and FHH. Genetic testing revealed a novel heterozygous CASR p.Tyr161* mutation and a homozygous SLC12A3 p.Thr60Met mutation, which ultimately confirmed the diagnosis of familial hypocalciuric hypercalcemia type 1 (FHH1) combined with GS.ConclusionFor the first time, we report a case of FHH combined with GS. The novel CASR mutation in this patient expands the variant spectrum of FHH, provides new genetic evidence for its pathogenesis, and underscores the importance of genetic counseling for consanguineous families. This case also suggests a potential association between FHH and CC, the mechanism of which warrants further investigation. In addition, this report highlights possible potential interactions between FHH and GS. Clinically, hypokalemia and hypomagnesemia associated with GS are more detrimental than hypercalcemia linked to FHH and should be prioritized in management. Finally, genetic testing and molecular diagnostics are crucial for pediatric and adolescent populations with FHH and/or GS, and further studies are needed to clarify the genotypic and phenotypic relationships between FHH and GS comorbidities.